Strategi Pemberdayaan Petenak melalui Program Pemanfaatan Biogas dalam Mewujudkan Desa Mandiri Energi di Kecamatan Musuk Kabupaten Boyolali - Nurtanti, Ina; Irawati, Diwi Acita; Ficky, Achmad Fahreza (Suluh Pembangunan : Journal of Extension and Development, 2024)
ABSTRACT The research aims to identify strategies for empowering farmers through biogas utilization programs in realizing Energy Independent Villages. This research was carried out in Sruni Village, Musuk District, Boyolali Regency, in March-April 2024. The method is a survey, the data collection technique in this study uses the Participatory Rural Appraisal (PRA) technique. Data from this study was collected through observation, interviews, and Focus Group Discussions (FGD). The sampling of this study was determined by a census of 45 people. The research data obtained was analyzed using SWOT analysis. The strength factors in this development program are the economic value of biogas is higher than other fuels, the value of biogas benefits is higher, the role of biogas in the value of environmental pollution The role of the government in the development of biogas. The weak factors in this business are the installation of biogas pipes that are easily clogged, and the maintenance of livestock is part-time. The opportunity factor of this program is to become a place of education and encourage the progress of the livestock sector. Threat factors such as perishable biogas installations and high gas pressure temperatures can cause explosions. The empowerment strategy of livestock farmer groups in Sruni Village, Musuk District, Boyolali Regency includes efforts to develop the creative economy, efforts to improve the quality of biogas, efforts to develop biogas installation technology, efforts to strengthen farmer members with groups, efforts to improve livestock business management, efforts to rehabilitate biogas as alternative energy. Keywords: biogas, energy independent villages, focus group discussion (FGD), participatory rural appraisal (PRA), empowerment strategy.